If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1s = 14 Solving 12 + -1s = 14 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1s = 14 + -12 Combine like terms: 12 + -12 = 0 0 + -1s = 14 + -12 -1s = 14 + -12 Combine like terms: 14 + -12 = 2 -1s = 2 Divide each side by '-1'. s = -2 Simplifying s = -2
| 98=-3(-2x-7)+5x | | 25g-5g^2=0 | | -4x+8=-2x+2 | | x+3x=2000 | | 5x(5x-4)= | | -4a+4(3a+3)=-8-2a | | 2y=6(-2)-10 | | p+1.6-0.4=-12 | | 2x+5y+2z=10.50 | | -5x^4+20x^2=0 | | 4x=-3x-7 | | 7y+6=180 | | 15=1.25h | | 8+8x+2x=2x+16 | | f(x-1)=x^2-14x+54 | | (2x+3.75)x-0.5=11.5 | | 3*8+2*-2= | | 6(3n-5)=(7n+6)+3 | | 9m^2+2m=10 | | 12+b=10 | | -54=a-49 | | 72=-6m | | Log(t-3)=(17-4t) | | (3x-18)(8x+32)=0 | | .5x^4-.5=0 | | -6p=58 | | -36g+40g+19g+-47g+18g=42 | | 3(8)+2(-2)= | | 1x+3y=78 | | -29=5u+6 | | 5x+7(-x+4)=14 | | 300=15w |